Morphometric study of human fibular incisura in dry bones - G Sreedevi; Muralidhar Reddy Sangam (Wolters Kluwer Medknow Publications, 2018)
Aims & Objectives: Interosseous border of tibia splits distally into anterior and posterior edges. These edges project into anterior and posterior tubercles enclosing a notch called fibular incisura that articulates with the distal fibula forming distal tibio fibular syndesmosis. The aim of the present study was to obtain the morphometric data of fibular incisura that may be helpful for the orthopedic surgeons in ankle reconstructive surgeries and ankle joint replacement. Materials & Method: To describe the morphometry of the fibular incisura, a total of 100 tibia [right 55 and left 45] were obtained from the Department of Anatomy, NRI Medical College, Chinakakani. The width of tibia, width, depth, height of fibular incisura and the length of anterior, posterior incisural tubercles were measured in both right and left tibia using digital vernier calipers. Right and left side para meters were compared using Karl Pearson Coefficient [r value]. Results: Average values for the width, depth and height of the fibular incisura were 16.83mm on the right side and 17.42mm on the left side, 2.85±1.38mm on the right and 2.9±1,57mm on the left side, 38.82±5.8mm on the right side and 38.72±7.68 mm on the left side respectively. While average lengths of anterior and posterior tubercles of the fibular incisura were 13.19±1.96mm, 15.71±2.03mm on the right side and 12.6±1.49mm, 15.66±1.41mm on left side. Thirty-three tibia presented deeply concave [depth>4cm], and sixty-seven had shallow fibular incisura [depth<4cm]. Conclusion: The morphometry and anatomical variability of fibular incisura should be taken to account in assessing radiographs, CT and MRI of talocrural joint.